Efficient Hyperchaotic Image Encryption Algorithm Based on a Fast Key Generation Method and Simultaneous Permutation-Diffusion Structure. (28th April 2022) - Ge, Bin; Chen, Gang; Chen, Xu; Shen, Zhihua
Abstract : To provide faster encryption speed for protecting image data privacy, a highly efficient hyperchaotic image encryption algorithm using a fast key generation method and simultaneous permutation-diffusion structure is proposed in this paper. Firstly, we design a novel fast key generation method to obtain four key matrixes with the size of W  ×  H ( W and H are the width and height of an image) with the hyperchaotic Lorenz system only iterating 2 W times. And within the key generation process, the piecewise linear chaotic map serves as a random selector to further enhance the randomness and unpredictability. Secondly, we introduce vectorization technique to parallelize the cipher blockchain-based encryption process. Hence, an image can be fast and sufficiently encrypted row by row and column by column through a four-round and interlinked diffusion process. Furthermore, during the diffusion process, the pixels are simultaneously scrambled by the Chebyshev map to enhance the antiattack capability of the proposed algorithm. Thirdly, we utilize a secure hash function to generate a plaintext-related secret key. Finally, cipher images can successfully pass common security tests with the correlation coefficients on the verge of 0, the entropies are greater than 7.99, and NPCR and UACI values are close to the expected values. Combined with other experimental results and analysis, we can safely conclude that the proposed algorithm has strong robustness against statistical, brute-force, differential, and some other common attacks. Moreover, only 0.009 s of encrypting a 256 × 256 image indicates that our algorithm has extensive application prosperity for real-time communications of massive digital images.